2001
DOI: 10.1070/rc2001v070n05abeh000656
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray synchrotron radiation in physicochemical studies

Abstract: Modern modifications of the conventional X-ray meth-Modern modifications of the conventional X-ray methods of physicochemical analysis (X-ray and electron spectroscopy, ods of physicochemical analysis (X-ray and electron spectroscopy, diffraction methods, diffraction methods, etc. etc.) and new combined techniques using) and new combined techniques using X-ray synchrotron radiation are considered. Unique character-X-ray synchrotron radiation are considered. Unique characteristics of synchrotron radiation are n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 183 publications
(187 reference statements)
0
8
0
Order By: Relevance
“…2) due to the proximity of atomic numbers of Hf (Z = 72) and rare-earth elements from La (Z = 57) to Dy (Z = 66). In order to enhance the contrast between the lanthanide and hafnium cations we used anomalous (resonant) x-ray diffraction [57,58]. It was found that the experimental intensity of the pyrochlore peaks are significantly altered for photon energies near the L 3 -Hf absorption edge (Fig.…”
Section: Anomalous X-ray Diffraction Analysismentioning
confidence: 99%
“…2) due to the proximity of atomic numbers of Hf (Z = 72) and rare-earth elements from La (Z = 57) to Dy (Z = 66). In order to enhance the contrast between the lanthanide and hafnium cations we used anomalous (resonant) x-ray diffraction [57,58]. It was found that the experimental intensity of the pyrochlore peaks are significantly altered for photon energies near the L 3 -Hf absorption edge (Fig.…”
Section: Anomalous X-ray Diffraction Analysismentioning
confidence: 99%
“…Exceptional characteristics of SR [17][18][19] allowed us to identify fluctuations in the arrangement of atoms in superstructural phases. The presence of domains of different degree ordering in the alloy matrix has led to a nontrivial form of diffraction profiles.…”
Section: Fig 2 Diffraction Patterns Foils At a Beam Energy Of Sr 20mentioning
confidence: 99%
“…There are several advantages for synchrotron radiation (SR) in comparison with X-ray tube radiation, including: brightness, high photon flux, level of monochromatization, easily adjusted X-ray wavelength, a high degree of polarization and collimation provide a new level of X-ray analysis as well as the quality of information acquisition [17][18][19]. Therefore, the aim of this study was to perform an X-ray diffraction study of membranes using SR with special attention to the region of small angles where order-disorder phase transitions occur in the Pd-In-Ru system after hydrogenation can be observed.…”
Section: Introductionmentioning
confidence: 99%
“…There are materials which contain transition metals (d-elements), lanthanides and actinides (f-and d&f-elements, correspondingly), [1][2][3] either as the atoms in a unit cell or point defects. Though a new era in investigating materials and defects containing heavy transition metals, lanthanides and actinides (d/f-elements below) was opened due to impressive recent achievements in creating experimental facilities like X-ray free-electron lasers, synchrotrons, 4,5 etc., to study local atomic-scale electronic structures in such materials, it remains most challenging for theoretical study to-date. First, a simultaneous treatment of relativistic and correlation effects at a very high level is required for their reliable calculations.…”
Section: Introductionmentioning
confidence: 99%